1990
DOI: 10.1007/bf01268019
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of radioimmunoguided surgery of colorectal carcinomas using indium-111 CEA-specific monoclonal antibody

Abstract: The study was undertaken to define the potential use of indium 111 carcinoembryonic antigen-specific antibody labelled [CEA F(ab')2] for the radioimmuno-detection of colorectal carcinoma using an intraoperative hand-held gamma probe. The use of a linear radioactive source allowed optimization of physical characteristics. The best results regarding sensitivity and resolution were obtained using a 5-mm thick tungsten alloy collimator. A simulation study with a liver phantom (22 MBq or 0.6 mCi) was performed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…7,12 Stable radionuclide enables ligands and covalent linkages that minimally alter the native MAb character. 13 In all MAbs in our study, radiochemical stability was acceptably maintained and they also exhibited high avidity of their radioimmune complex from a close correlation of immune complex and silver grains in tumors. Radionuclides most suitable for the detection of small superficial tumors should emit radiation with little penetration and have a sufficiently long half-life to allow blood clearance of radioactivity so as to obtain relatively elevated tumor-to-blood ratio.…”
Section: Discussionmentioning
confidence: 50%
“…7,12 Stable radionuclide enables ligands and covalent linkages that minimally alter the native MAb character. 13 In all MAbs in our study, radiochemical stability was acceptably maintained and they also exhibited high avidity of their radioimmune complex from a close correlation of immune complex and silver grains in tumors. Radionuclides most suitable for the detection of small superficial tumors should emit radiation with little penetration and have a sufficiently long half-life to allow blood clearance of radioactivity so as to obtain relatively elevated tumor-to-blood ratio.…”
Section: Discussionmentioning
confidence: 50%
“…In the present study T/B ratios varied considerably between the different scintigraphy-positive neuroendocrine tumour types; in MC tumours the ratio was 27-650, in a gastric carcinoid 71-210, in MTC 3-39 and in EPT 910 -1500. These high ratios would be expected to facilitate detection of tumours with intraoperative scintillation detection in comparison with, for example, radioimmunoguided surgery using radiolabelled monoclonal antibodies (Curtet et al, 1990;Sardi et al, 1989). Earlier limited studies on probe-guided surgery using radiolabelled octreotide in patients with neuroendocrine tumours (Ahlman et al, 1994;Schirmer et al, 1993;Waddington et al, 1994) have been promising in individual patients.…”
Section: Statistical Analyses Of Intraoperative Measurementsmentioning
confidence: 99%
“…For accurate localization it is desirable that low-energy radionuclides are employed [1][2][3]19]. The use of highenergy radionuclides reduces the specificity of the procedure since problems arise from scattered radiation from sites of high normal uptake of tracer, such as the liver [3].…”
mentioning
confidence: 99%
“…The use of highenergy radionuclides reduces the specificity of the procedure since problems arise from scattered radiation from sites of high normal uptake of tracer, such as the liver [3]. Reports of radioimmunoguided surgery utilizing ~ ~ tin have concluded that the routine use of lower-energy radionuclides would be preferablein addition to more specific antibodies with higher tumour to normal tissue uptake [3,7], The use of 12~I for radioimmunoguided surgery (RIGS) appeared to be attractive from a physical point of view [1,2,19], but would appear to be contraindicated for routine use because of the high patient radiation-absorbed dose [3]. This therefore eliminates the routine use of lalI and 11 ~In, which have commonly been used for radiolabelling antibodies.…”
mentioning
confidence: 99%
See 1 more Smart Citation